Perbandingan karakteristik morfometrik induk kerbau yang dipelihara secara intensif dan semi intensif di Desa Kejambon dan Desa Surajaya - Edhiningtyas, Chrisshinta Iris; Hasanah, Himmatul (Filogeni: Jurnal Mahasiswa Biologi, 2024)
Breeders with superior genetics will pass on the gene to the next generation. Efforts to improve the genetic quality and livestock population require selection of breeders to improve good livestock performance. This study aims to determine the comparison of livestock body size with the size required in SNI and the comparison of buffalo with intensive and semi-intensive maintenance systems. This study used a purposive sampling method for sampling. The samples used were pregnant and lactating breeders in Kejambon Village and Surajaya Village. Differences in maintenance systems for female and lactating breeders were analyzed using the t-test. The results showed that the Body Scoring Condition (BCS) value was not significantly different (P>0.05). The body size of pregnant female breeders showed a significant difference (P<0.05) except for shoulder height and body weight. While in lactating female breeders, all parameters were not significantly different (P>0.05). The conclusion is that BCS observations show that pregnant and lactating breeders that are intensively and semi-intensively maintained meet the standards as breeders. In the morphometric measurements of the body of female and pregnant breeders that are intensively and semi-intensively maintained, all meet the standards in SNI. The morphometry of pregnant sows kept intensively was higher than that of semi-intensive sows, while that of lactating sows kept intensively was lower than that of semi-intensive sows.